Exploratory Study of the Awareness on Diabetes Mellitus - Humaira, Abdul Latif; Noor Azlinna, Azizan; M. R., Abdul Hamid (UTM Press, 2016)
Diabetes is a steadily growing problem in Malaysia and the increase of diabetic’s patients in Malaysia is worrisome. The cause of diabetes is a mystery, although both genetics and environment appear to play roles. Therefore, this study aimed to test Diabetes Mellitus Awareness Model (DMAM) that consists of several latent factors i.e. knowledge, attitude, environment, symptom and diabetes awareness. Ten hypotheses have been proposed to test the relationship between five indicators in the model. Partial Least Squares-Structural Equation Modelling (PLS-SEM) technique was used by using the SmartPLS software to analyse the model. The study was conducted at two health clinics under Ministry of Health (MOH) in Pahang. A convenience sample of 441 adults was obtained for this study. The result shows that knowledge has a significant impact on environment, attitude and awareness. Likewise, environment significantly influences the attitude and attitude significantly influences awareness. However, the study also found that there was no significant relationship between knowledge towards symptoms, environments towards awareness and symptom, attitude towards symptoms and symptoms towards awareness. Overall, this study concludes that the relationships that are statistically significant should be taken due care by the health authorities in order to raise diabetes awareness through indicator in the model.